Reform of The Inheritance System: Between Islamic Law and Tradition of Sasak Tribe - Fikri, Muhammad (De Jure: Jurnal Hukum dan Syari'ah, 2024)
This paper discusses the reform of the inheritance system between Islamic law and tradition of the Sasak tribe by investigating how religious leaders in Lombok view the inheritance distribution system and how to reform the inheritance system between Islamic law and tradition in the Sasak Lombok Community. This research uses qualitative methods with a case study approach, and data taken from the field was analysed using Jasser Auda's system theory regarding maqasid sharia. The result of reforming the Islamic law system and tradition in the Sasak tribe is to eliminate injustice within the Lombok NTB community by emphasising the value of inheritance property rather than its quantity. This approach ensures that inheritance distribution considers the value of assets, such as land, rather than merely dividing by area. For instance, the value of one hectare of strategically located land differs significantly from that of less strategically located land. Thus, instead of dividing the land by hectares, it is divided based on value, ensuring a fair distribution among the eldest brother, other brothers, and sisters. This method seeks to achieve justice for all parties involved.